Cofactor-Activated Phosphorylation Is Required for Inhibition of Cortical Neuron Differentiation by Groucho/TLE1 - Buscarlet, Manuel (Public Library of Science, 2009)
BACKGROUND: Transcriptional co-repressors of the Groucho/transducin-like Enhancer of split (Gro/TLE) family regulate the expression of a variety of genes and are involved in numerous developmental processes in both invertebrate and vertebrate species. More specifically, Gro/TLE1 participates in mechanisms that inhibit/delay the differentiation of cerebral cortex neural progenitor cells into neurons during mammalian forebrain development. The anti-neurogenic function of Gro/TLE1 depends on the formation of protein complexes with specific DNA-binding transcription factors that engage Gro/TLE1 through WRP(W/Y) sequences. Interaction with those transcription partners results in Gro/TLE1 recruitment to selected DNA sites and causes increased Gro/TLE1 phosphorylation. The physiological significance of the latter event, termed “cofactor-activated phosphorylation,” had not been determined. Therefore, this study aimed at clarifying the role of cofactor-activated phosphorylation in the anti-neurogenic function of Gro/TLE1. METHODS AND PRINCIPAL FINDINGS: A combination of site-directed mutagenesis, mass spectrometry, biochemistry, primary cell culture, and immunocytochemical assays was utilized to characterize point mutations of Ser-286, a residue that is phosphorylated in vivo and is located within the serine/proline-rich (SP) domain of Gro/TLE1. Mutation of Ser-286 to alanine or glutamic acid does not perturb the interaction of Gro/TLE1 with DNA-binding partners, including the basic helix-loop-helix transcription factor Hes1, a prototypical anti-neurogenic WRP(W/Y) motif protein. Ser-286 mutations do not prevent the recruitment of Gro/TLE1 to DNA, but they impair cofactor-activated phosphorylation and weaken the interaction of Gro/TLE1 with chromatin. These effects are correlated with an impairment of the anti-neurogenic activity of Gro/TLE1. Similar results were obtained when mutations of Ser-289 and Ser-298, which are also located within the SP domain of Gro/TLE1, were analyzed. CONCLUSION: Based on the positive correlation between Gro/TLE1 cofactor-activated phosphorylation and ability to inhibit cortical neuron differentiation, we propose that hyperphosphorylation induced by cofactor binding plays a positive role in the regulation of Gro/TLE1 anti-neurogenic activity.